TINDAK TUTUR DIREKTIF DAN EKSPRESIF SISWA DAN GURU DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA INDONESIA MUDA - Putri, Misyati Tri; Patriantoro, Patriantoro; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe background of this research is that directive and expressive speech acts are pragmatic studies. The problem in this research is the form of directive speech acts of students and teachers in learning Indonesian in class X IIS Indonesia Young High School and expressive speech acts of students and teachers in learning Indonesian in class X IIS Indonesia Young High School. The benefits of this research are divided into two namely theoretical benefits and practical benefits.The method used in this research is descriptive method in the form of qualitative research. Data collection techniques used in this study were observation, peer, and video. The tools used in this study are mobile phones and stationery. The results of the analysis contained 76 directive and expressive speech acts of Indonesian students and teachers in class X IIS of Indonesia Young High School. Forms of directive speech acts requestives 12 data, forms of directive speech acts questions 24 data, forms of directive speech acts requirements 22 data, forms of directive speech acts permissives 4 data, forms of directive speech acts of advisories 10 data and forms of expressive speech acts 4 data. Keywords: Directive and Expressive Speech Acts, Speaking, Speech Acts